Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let us solve the given equation step by step.
The given equation is:
[tex]\[ 2(7x + 4) = 4x - 6(2 - x) + 7 \][/tex]
First, distribute the constants on both sides of the equation.
For the left side:
[tex]\[ 2(7x + 4) = 2 \cdot 7x + 2 \cdot 4 = 14x + 8 \][/tex]
For the right side:
[tex]\[ 4x - 6(2 - x) + 7 = 4x - 6 \cdot 2 + 6 \cdot x + 7 = 4x - 12 + 6x + 7 = 10x - 5 \][/tex]
Now, the equation is simplified to:
[tex]\[ 14x + 8 = 10x - 5 \][/tex]
Next, combine like terms by moving all terms involving [tex]\( x \)[/tex] to one side of the equation and the constant terms to the other side.
Subtract [tex]\( 10x \)[/tex] from both sides:
[tex]\[ 14x - 10x + 8 = -5 \][/tex]
Simplify it to:
[tex]\[ 4x + 8 = -5 \][/tex]
Subtract 8 from both sides to isolate the terms involving [tex]\( x \)[/tex]:
[tex]\[ 4x = -5 - 8 \][/tex]
Simplify it further:
[tex]\[ 4x = -13 \][/tex]
Finally, solve for [tex]\( x \)[/tex] by dividing both sides by 4:
[tex]\[ x = \frac{-13}{4} \][/tex]
Therefore, the solution to the equation is:
[tex]\[ x = -\frac{13}{4} \][/tex]
The correct choice is:
B. [tex]\( x = -\frac{13}{4} \)[/tex]
The given equation is:
[tex]\[ 2(7x + 4) = 4x - 6(2 - x) + 7 \][/tex]
First, distribute the constants on both sides of the equation.
For the left side:
[tex]\[ 2(7x + 4) = 2 \cdot 7x + 2 \cdot 4 = 14x + 8 \][/tex]
For the right side:
[tex]\[ 4x - 6(2 - x) + 7 = 4x - 6 \cdot 2 + 6 \cdot x + 7 = 4x - 12 + 6x + 7 = 10x - 5 \][/tex]
Now, the equation is simplified to:
[tex]\[ 14x + 8 = 10x - 5 \][/tex]
Next, combine like terms by moving all terms involving [tex]\( x \)[/tex] to one side of the equation and the constant terms to the other side.
Subtract [tex]\( 10x \)[/tex] from both sides:
[tex]\[ 14x - 10x + 8 = -5 \][/tex]
Simplify it to:
[tex]\[ 4x + 8 = -5 \][/tex]
Subtract 8 from both sides to isolate the terms involving [tex]\( x \)[/tex]:
[tex]\[ 4x = -5 - 8 \][/tex]
Simplify it further:
[tex]\[ 4x = -13 \][/tex]
Finally, solve for [tex]\( x \)[/tex] by dividing both sides by 4:
[tex]\[ x = \frac{-13}{4} \][/tex]
Therefore, the solution to the equation is:
[tex]\[ x = -\frac{13}{4} \][/tex]
The correct choice is:
B. [tex]\( x = -\frac{13}{4} \)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.